The role of family-school relationship in promoting preschoolers’ classroom engagement - Shen, Luyou (Frontiers in Psychology, 2025)
In 1993, Finn proposed in his paper that classroom engagement can be described from three dimensions. Subsequently, research on children’s classroom engagement gradually gained attention. Although previous literature has explored the factors that affect classroom participation, most studies only focus on the influence of family or school, rarely considering the family-school relationship as a whole. This study aims to address this deficiency by systematically reviewing literature and using the PRISMA search strategy to exclude non-English literature, books, and conference papers. I have also developed three screening criteria: (1) research topic is not on home-school relationship; (2) research topic is not on students’ participation; (3) research participants are not preschool children. Finally, 17 relevant articles were selected for analysis. Research has founfd that good family-school relationship can enhance children’s classroom participation, manifested in parents accompanying their children more in learning, helping them improve social skills and develop good habits. Parents and teachers will trust each other, reduce information gaps, and enhance children’s psychological security. And they will cooperate to provide opportunities for children to exercise their cognitive abilities and enhance their cognitive participation. This study provides valuable reference for educators in the field of preschool education to understand the relationship between family-school relationship and children’s classroom participation. Therefore, educators are able to adjust their educational strategies and design courses that can fully mobilize children’s enthusiasm and help them grow.